Characterisation of layered scattering media using polarized light - Stockford, Ian M (2004)
This thesis investigates the properties of backscattered polarized light from layered scattering media with a view to application in the imaging of in-vivo skin for medical application. The research includes investigation of numerically simulated samples, tissue phantoms and in-vivo tissue.